The Huguenots in the French Economy, 1650-1750 - Scoville, Warren C. (Quarterly Journal of Economics, 1953)
I. Introduction, 423. — II. The place of the Protestant nobility and peasantry, 424. — III. The Protestant bourgeoisie; its economic superiority and commercial importance, 426. — IV. Its industrial position; its rôle in private and public finance, 430. — V. Various hypotheses as to the generalized relationship of Protestantism and capitalism, 432. — VI. Predestination and man's calling. Protestantism and individualism. Rationalization of economic activity. Attitude toward interest, 435. — VII. The Huguenots as a "penalized minority, " 439. — VIII. Conclusions, 443.